PERPUSTAKAAN ADALAH SALAH SATU TEMPAT PEMBELAJARAN SEPANJANG HAYAT - Najla Rustam; Arin Khairunnisa (Nusantara Hasana Journal, 2023)
The learning process through formal channels is often age-limited, while the independent learning process ("lifelong learning") takes place independently with the support of many sources of information available in the library. Learning and the library are two things that support each other and are related, which is in accordance with one of the functions of the library as a place for learning and the library as a means to optimize continuous learning. Habituation patterns that help the learning process are reading and looking for reference sources that are useful in pursuing intellectual interests. The mission of the library as a place for lifelong learning is not only waiting for users, but also playing an active role in stimulating users, creating service innovations, and making users feel at home in the library and have a special preference for the library.